Couriers and drivers – women or men? Opinions on gender in platform work “via apps” in Poland - Tusińska, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
The article examines gender-related perceptions and stereotypes of platform-based courier and driver jobs, focusing on factors such as physical aptitude, safety concerns, work flexibility, and anonymity. The theoretical background to the empirical research was the theory of statistical discrimination. The main purpose was to provide the views of Polish residents on gender diversity in the context of platform work as couriers for delivering meals from restaurants or shopping and taxi drivers. The following hypothesis was set: clients might be guided by stereotypes in their opinions given to platforms workers. The methods used were critical analysis of the scientific achievements of literature and a diagnostic survey, using the questionnaire technique. The paper explores the concept of digital labour platforms (DLPs) focusing on offline service delivery and provides a concise overview of statistical discrimination theory. It also examines the results of a survey conducted among adult inhabitants of Polish cities. The findings indicate that while certain gendered perceptions remain strong, attitudes seem to be not far away from gender neutrality.

Przedmiotem badań w artykule uczyniono stereotypy związane z płcią w kontekście pracy kurierów i kierowców świadczących usługi za pośrednictwem platform cyfrowych (DLP), koncentrując się na takich aspektach, jak predyspozycje fizyczne, kwestie bezpieczeństwa, elastyczność pracy oraz anonimowość. Teoretycznym punktem odniesienia dla badań empirycznych była teoria dyskryminacji statystycznej. Głównym celem było przedstawienie opinii mieszkańców Polski na temat kobiet i mężczyzn w kontekście pracy platformowej, tj. jako kurierzy dostarczający posiłki z restauracji lub zakupy oraz jako kierowcy taksówek. Postawiono następującą hipotezę: klienci platform mogą kierować się w swoich ocenach pracowników stereotypami dotyczącymi płci. Zastosowane metody badawcze obejmowały krytyczną analizę dorobku literatury naukowej oraz metodę sondażu diagnostyczny z wykorzystaniem techniki ankietowej. W artykule omówiono pojęcie cyfrowych platform pracy z akcentem na usługi realizowane offline i przedstawiono krótką charakterystykę teorii dyskryminacji statystycznej. Dokonano analizy wyników badania ankietowego przeprowadzonego wśród dorosłych mieszkańców polskich miast. Można stwierdzić, że choć pewne stereotypy płciowe nadal są obecne, postawy respondentów nierzadko bywają neutralne.
Kurierzy i kierowcy – czy płeć ma znaczenie? Opinie na temat kobiet i mężczyzn w pracy platformowej w Polsce
Keywords: digital labour platforms; gender inequality; work “via apps”; couriers; drivers; cyfrowe platformy usług pracy; nierówności płci; praca przez aplikację; kurierzy; kierowcy